PENGARUH PENGGUNAAN KB SUNTIK 3 BULAN TERHADAP PENINGKATAN BERAT BADAN AKSEPTOR - Kadek Dwi Ariesthi (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2019)
At Fatululi Assistant Health Center in the period July to December 2016 there were 60 family planning acceptors who experienced weight gain as a side effect of using KB. This study aimed to analyze the effect of using 3-month injection KB on increasing acceptor body weight. Descriptive research using the survey method was carried out from September to October 2017 in the work area of ​​Fatululi Assistant Health Center, Kota Lama District, Kupang City, NTT. Samples are acceptors who have used 3-month injection KB at least three times, with 30 acceptors. Data collected is secondary data. Data analysis is done univariately. The results showed an average increase in body weight in the first 3 months of injection contraception was 1.8 kg, the average increase in body weight in the first 6 months was 2.6 kg and the average for the first 9 months was 4.6 kg. The use of 3-month injection of KB affects weight gain. Keywords: Acceptor, Injection KB, Weight Gain